Isolation and cloning of cytokinin oxidase 5 gene from Arabidopsis - Repalli, Sai Krishna; Baruah, Ananta M; Rai, Rhitu; Dash, Prasanta K. (Annals of Agricultural Research, 2016)
Phytohormones play intricate physiological and biochemical roles to control growth anddevelopment of plants. Amongst several phytohormones cytokinins (CKs) play an important roleas they govern yield in crops. While controlling cardinal growth of plants, CKs govern a complextrait i.e. shoot apical meristem formation and there by yield in crops. Mutation studies on cytokininoxidase (ckx) genes had revealed that decreased activity of cytokinin oxidase results in increasedbioavailability of cytokinin and thereby increasing seed yield. In this study, we isolated ckx5gene from Arabidopsis and cloned into an E coli vector so as to make it ready for mobilization intobinary vector for future plant transformation experiments. Sequence of steps followed to clonethe gene from Arabidopsis and confirm its presence were ncomphishel by (i) PCR based amplificationwith gene specific primers, (ii) restriction digestion followed by (iii) authentication of ckx gene bySanger's DNA-sequencing are discussed.